2021
DOI: 10.1002/rob.22017
|View full text |Cite
|
Sign up to set email alerts
|

A more precise way to localize animals using drones

Abstract: Radio telemetry is a commonly used technique in conservation biology and ecology, particularly for studying the movement and range of individuals and populations. Traditionally, most radio telemetry work is done using handheld directional antennae and either direction‐finding and homing techniques or radio‐triangulation techniques. Over the past couple of decades, efforts have been made to utilize unmanned aerial vehicles to make radio‐telemetry tracking more efficient, or cover more area. However, many of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Corcoran et al (2021) found that automated wildlife detection using drones can be achieved for a wide range of species (e.g., koala Phascolarctos cinereus; glossy ibis Plegadis falcinellis) and under various ecological conditions (e.g., low dense eucalyptus forest, coastal wetlands). This is corroborated by several studies from different ecosystems, for example, coastal (Oosthuizen et al, 2020), marine (Dickens et al, 2021) and inland (Eori et al, 2020;Hui et al, 2021). Hollings et al (2018 pointed out a potential constraint to using drones for automated wildlife detection is that accuracy often reduces over larger spatial scales, and the cost of high-resolution data is relatively high.…”
Section: Wildlife Surveillancesupporting
confidence: 71%
“…Corcoran et al (2021) found that automated wildlife detection using drones can be achieved for a wide range of species (e.g., koala Phascolarctos cinereus; glossy ibis Plegadis falcinellis) and under various ecological conditions (e.g., low dense eucalyptus forest, coastal wetlands). This is corroborated by several studies from different ecosystems, for example, coastal (Oosthuizen et al, 2020), marine (Dickens et al, 2021) and inland (Eori et al, 2020;Hui et al, 2021). Hollings et al (2018 pointed out a potential constraint to using drones for automated wildlife detection is that accuracy often reduces over larger spatial scales, and the cost of high-resolution data is relatively high.…”
Section: Wildlife Surveillancesupporting
confidence: 71%
“…The average distance between the detected points and the nanotag location ranged from 29 m to 35 m. However, the distance between the geographic center and the nanotag location, excluding detection number one, ranged from 7 m to 16 m. Based on the calculation of the geographic center, it was found that the location of the nanotag could be estimated with an accuracy of less than 16 m. However, more than three detections are needed to guarantee the accuracy of the estimation. The location estimation accuracy of the previous study is 22.7 ± 13.9 m [17] and 25.9 ± 25.2 m [18], and the accuracy of our system can be said to be high. If we use the drone radio telemetry system used in this study to track the frogs at a high frequency, we will be able to track the frog's movements if they move more than about 16 m.…”
Section: Spatial Accuracy Of Nanotag Detection Pointsmentioning
confidence: 66%
“…In addition, although only nanotags were installed in this study, the size of the target animal may have affected the detection performance when the tags were attached to the animals. Few studies have actually used the drone radio telemetry system to track organisms [18]. In the future, it will be necessary to continue verifying in various environments and animals to further clarify the relationship between the location of the target animal and the detection performance.…”
Section: Future Workmentioning
confidence: 99%
“…Localizing a particular signal source finds many applications in real life. In wildlife studies, animals with a radio transmitter can be tracked, thus the examination of their natural life can be achieved in a short time without the possibility of entering dangerous areas and encountering animals by using the aerial robots in Bayram, Doddapaneni et al (2016), Bayram et al (2018), Hui et al (2021), and Nguyen et al (2019). These tracked animals can also be invasive fish species.…”
Section: Introductionmentioning
confidence: 99%